Thinking the unthinkable: an anthropological note on war - Ramos Castro, David (Razón y fe, 2022)
The war between Russia and Ukraine challenges the whole of us in our historical and cultural condition at the present. In addition to another sign of historical acceleration, it obliges us to think about the definitive consequences of a possible world war whose atomic and nuclear forces could annihilate the entire planet. In this article I reflect on this from an anthropological point of view. It is a perspective justified by the total threat to all forms of life, by the techno-scientific hegemony that has increased it and by the inability to create a global culture that does not start from the old and reductive political opposition between friend and enemy, and that refutes the supposedly unavoidable aggressiveness of the human animal as something independent of its socio-cultural conditions. Such incapacity manifests itself in the parallel war of media images in their presentation of the Other and in which the West has confused the notions of visibility, power, and influence with its more recent uses of them. The possible end result, which we should think more about the more unthinkable it would seem to us, would mean not only the extinction of all future, but the annihilation of all that was, as if we had never existed.
Keywords: anthropology; nuclear war; annihilation; image; visibility; power; media; influence